BEACONS of the UMMAH Tracing the Footsteps of Singapore's Islamic Religious Leaders. - Singapore Islamic Scholars and Religious Teachers Association (PERGAS); Sundusia Rosdi content developer 631838; Nurhafizah Azman content developer 631858; Khairunnisaa Abdul Rahman content developer 631859; Haslina Sabar content developer 631844; Khalidah Md. Jamil translator 631860; Lina Abdul Wahab translator 631861; Nur 'Aini Zulkifli proof reader 631862 (Singapore : Persatuan Ulama dan Guru-guru Agama Islam Singapura (PERGAS), 2019)
A record of the vast contributions of Islamic religious leaders in Singapore, who consist of religious teachers (asatizah), scholars, and Muslim leaders. They helped in spreading the message of Islam, served as beacons of knowledge and were at the heart of the development of Islam in Singapore from as early as the 15th Century.